In Vitro Characterization of Acute Pain and Wound Healing In a Silk-Based Cornea Model. - Pollard, Rachel E. (Tufts Archival Research Center, 2018)
The cornea is the most densely innervated peripheral tissue in the body, as detection of slight changes in the chemical, thermal, and physical environments of the ocular surface is necessary to protect eyesight. Damage to the cornea as a result of caustic chemical exposure can be painful and debilitating, underscoring the need for understanding ocular irritation mechanisms. The 3D in vitro silk-based cornea model developed by Wang et al (2017) is a novel tool for studying pain in the cornea as it is the first engineered cornea model to incorporate epithelium, keratocytes, and human sensory nerves in 3D scaffolding. In these studies this model was used to study the effects of pain and irritation mediated by transient receptor potential (TRP) channels vanilloid 1 and ankyrin 1 (TRPV1, TRPA1) using a variety of stimuli. The results show that this model is a viable tool for studying pain responses in vitro in a holistic, high throughput-like manner and shows promise as a novel and sensitive tool for studying chemical irritation.